Adolescent Neglect and Health Risk. (May 2022) - Kobulsky, Julia M.; Villodas, Miguel; Yoon, Dalhee; Wildfeuer, Rachel; Steinberg, Laurence; Dubowitz, Howard
This study examined relationships between adolescent neglect and abuse and later health risk in a sample of 1050 youth (53% female, 56% Black, and 24% White) from the Longitudinal Studies of Child Abuse and Neglect. At age 16, the youth reported any adolescent exposure to neglect and physical, sexual, and emotional abuse. At age 18, they reported risk behaviors (delinquency, substance use, and sexual behavior) and emotional and behavioral problems (externalizing and internalizing problems, suicidality). Control variables were childhood maltreatment (self-reports and early childhood child protective services reports), risk behaviors and emotional and behavioral problems at age 16, and demographics. Analysis confirmed a 5-factor model of adolescent neglect (Exposure to Risk, Inadequate Monitoring, Inattention to Basic Needs, Permitting Misbehavior, and Inadequate Support). Inadequate Support and Exposure to Risk were associated with more substances used; Exposure to Risk was also associated with delinquency and suicidality. Adolescent emotional abuse was associated with not using a condom use and internalizing and externalizing problems. Findings underscore the importance of preventing or addressing neglect during adolescence.